Modeling a satisficing judge - Christoph Engel; Werner Güth (Max Planck Institute for Research on Collective Goods, 2015)
Judges and juries frequently must decide, knowing that they do not know everything that would be relevant for deciding the case. The law uses two related institutions for enabling courts to nonetheless decide the case: the standard of proof, and the burden of proof. In this paper, we contrast a standard rational choice approach with a satisficing approach. Standard theory would want judges to rationally deal with the limitations of the evidence. We posit that this is not only descriptively implausible, but also normatively undesirable. We propose a theoretical framework for a judge who only considers scenarios that "she does not dare to neglect", and aims at decisions that are "good enough", given the undissolvable limitations of the evidence. We extend this approach to parties who strategically exploit the limited factual basis, and to judges who have to allocate limited resources for fact finding to more than one case.
Keywords: D82; C72; D81; K41; D03; 330